2016
DOI: 10.1093/bib/bbw053
|View full text |Cite
|
Sign up to set email alerts
|

Screening and validation of lncRNAs and circRNAs as miRNA sponges

Abstract: Intensive research in past two decades has uncovered the presence and importance of noncoding RNAs (ncRNAs), which includes microRNAs (miRs) and long ncRNAs (lncRNAs). These two classes of ncRNAs interact to a certain extent, as some lncRNAs bind to miRs to sequester them. Such lncRNAs are collectively called 'competing endogenous RNAs' or 'miRNA sponges'. In this study, we screened for lncRNAs that may act as miRNA sponges using the publicly available data sets and databases. To uncover the roles of miRNA spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
231
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(238 citation statements)
references
References 47 publications
7
231
0
Order By: Relevance
“…These results indicate that the altered expression of salivary hsa_circ_0001874 and hsa_circ_0001971 may be related to their involvement in the development and progression of OSCC. Studies have revealed that circRNAs can serve as a miRNA sponge and can interact with miRNA, resulting in an imbalance between miRNA and its target genes, which leads to the initiation and progression of a variety of diseases including cancer [28,29]. The relationship between miRNAs and OSCC suggest that circRNAs might be involved in the pathogenesis and progression of OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the altered expression of salivary hsa_circ_0001874 and hsa_circ_0001971 may be related to their involvement in the development and progression of OSCC. Studies have revealed that circRNAs can serve as a miRNA sponge and can interact with miRNA, resulting in an imbalance between miRNA and its target genes, which leads to the initiation and progression of a variety of diseases including cancer [28,29]. The relationship between miRNAs and OSCC suggest that circRNAs might be involved in the pathogenesis and progression of OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Lower circulating level of miR‐150 might be a novel marker for left ventricular remodeling in AMI patients (Devaux et al, ). Note that lncRNAs can interact with miRNAs and then exert their biological function as miRNA sponges (Militello et al, ). So we speculated that ZFAS1 might regulate the expression of miR‐150, which was a multifunctional molecular in AMI animal models.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, salmena and colleagues proposed a competing endogenous RNA (ceRNA) hypothesis that lncRNAs, mRNAs and other RNAs act as natural miRNA sponges to suppress miRNA function by using shared MREs [8]. This hypothesis has been validated experimentally by some researchers that lncRNA functioned as ceRNA to communicate with mRNAs through competing for shared miRNAs [9]. LncRNAs that harbor similar sequence to their targeted miRNAs, can sequester miRNAs away from mRNAs.…”
Section: Introductionmentioning
confidence: 99%